Comparative Analysis of Monetary Policy on Price Stability in Three Asean Countries: Seemingly Unrelated Regression (Sur) Approach for the Period 2015-2024 - Chairuddin Chairuddin; Rusiadi Rusiadi; Andria Zulfa (Utan Kayu Publishing, 2025)
This study aims to analyze the effectiveness of monetary policy transmission on inflation in ASEAN-3 countries. This topic is relevant considering the differences in economic structures and monetary policy frameworks in the region that have the potential to produce a heterogeneous inflation response. This study tests the hypothesis that monetary policy instruments, including policy interest rates, money supply, exchange rates, and credit growth, influence inflation. The research method used is a quantitative approach with a Seemingly Unrelated Regression (SUR) model using annual secondary data. The results show that policy interest rates have a significant effect on inflation, while money supply, exchange rates, and credit growth do not. This finding indicates that monetary policy transmission in ASEAN-3 is more effective through the interest rate channel than other monetary channels. This study provides an empirical contribution to strengthening understanding of the role of monetary policy instruments in maintaining inflation stability in developing countries